Software Framework for Mitigating Programming Plagiarism and Collusion - Karnalim, Oscar (Informatica, 2026)
Many mitigation strategies for programming plagiarism and collusion focus solely on either penalising students involved in such misbehaviour or manually educating students regarding the matter. This paper combines both strategies within a software framework and automates the education strategy. It informs students about plagiarism and collusion based on code similarity and instructors' expectations through an assessment submission system with three variants. Highly similar submissions are alerted, while original submissions have their similarities simulated. In addition, the quality of the submissions is also reported through static analysis. On the due date, student submissions are checked using a similarity detector that provides human-language explanations, which has two variants. Students using our framework show greater awareness of programming plagiarism and collusion, and are less likely to engage in such misbehaviours.
Keywords: academic integrity; learning technology; computing education; code similarity